2015
DOI: 10.1002/gps.4335
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Alzheimer's disease testing of Australian general practice patients: a cross-sectional questionnaire-based study

Abstract: This study demonstrates that a majority of patients would like to know if they have AD. Acceptability of testing modalities, however, varies. Noninvasive, familiar methods are more acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…Lawrence and colleagues observed that diagnostic confirmation was an important incentive for participation among cognitively impaired older adults [40]. Findings are nevertheless inconsistent [44,45]. Although a perceived high risk of AD was associated with increased interest in receiving information about one's genetic and/or diagnostic status [46], the opposite was true for individuals with self-reported cognitive complaints or family history of AD [46] and former caregivers of AD patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence and colleagues observed that diagnostic confirmation was an important incentive for participation among cognitively impaired older adults [40]. Findings are nevertheless inconsistent [44,45]. Although a perceived high risk of AD was associated with increased interest in receiving information about one's genetic and/or diagnostic status [46], the opposite was true for individuals with self-reported cognitive complaints or family history of AD [46] and former caregivers of AD patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…We found that it was most common to measure biomarkers at 2 points in time, with very few studies repeating measures more than twice. This can be attributed to the high costs of the measures used [ 20 ] or the invasiveness of CSF sample collection [ 140 ]. Earlier and more frequent measures would facilitate more robust conclusions to be drawn on the precise timing and etiology of AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Patients themselves have a range of views about this, and a large minority are not keen to be diagnosed with dementia. 3 Indeed, the diagnosis is a grim one of a terminal illness with progressive deterioration. However, as with other terminal illnesses, it may be helpful for a person to know what is happening: while they still have capacity, they can complete their advance care planning (will, appointment of health and financial spokespeople, advance care directive), fulfil 'bucket list' plans and perhaps access anti-dementia medications and implement diet and exercise interventions to slow progression.…”
Section: Why Assess Cognitive Impairment?mentioning
confidence: 99%